Drug-induced metabolic acidosis. (June 2017) - Holt, Christopher T.; Hitchings, Andrew W.
Abstract : Summary: Drug causes of metabolic acidosis are numerous and their mechanisms are diverse. Broadly, they can cause metabolic acidosis with either a normal anion gap (e.g. drug-induced renal tubular acidosis) or an elevated anion gap (e.g. drug-induced lactic acidosis or pyroglutamic acidosis). This review describes the drugs that can cause or contribute to metabolic acidosis during therapeutic use, the mechanisms by which this occurs, and how they may be identified in practice.